Centrosome amplification in tumorigenesis - Anderhub, Simon; Krämer, Alwin; Maier, Bettina (Cancer letters, 2012)
With regard to cancer development the centrosome has been the center of attraction of scientists for already more than a 100 years. After the initial assumption that amplified centrosomes and abnormal mitotic arrangements might be a cause of cancer at the beginning of the last century, enormous efforts have been undertaken to clarify the relevance of centrosome amplification in tumorigenesis. In the meantime, centrosome amplification has been observed in most, both solid and hematological, cancer entities and by now is viewed as a "hallmark" of cancer cells. In this review we summarize basics in centrosome biology and what is known about the emergence of amplified centrosomes. In addition, we discuss how centrosome amplification might cause aneuploidy thereby leading to malignant transformation of cells. Furthermore, we present recent insights into the role of centrosome amplification in tumor formation based on work in model systems.